GAFA in the Time of Pandemic: A Performance Analysis - Michal GOLINSKI (Communications of International Proceedings, 2022)
In the last two decades, digital platforms have become digital multiverse hubs, concurrently changing the economy, society, culture and politics. They make our daily lives enormously easier, and they do so by grabbing our attention and constantly collecting more and more data. Not only do these data allow platforms to fully understand our characteristics, but they also let them accurately predict our future behaviour. Regarding the economic sphere, platforms are intensifying the processes of digital destruction, rendering many products, companies or industries obsolete as a result of major changes in the needs, expectations and behaviours of market participants.  The aim of this article is to analyse the functioning of the largest digital platforms, referred to as GAFA, in the COVID-19 pandemic situation. The main research questions for the study period are: What has the economic performance of these corporations been like? Has their development been in line with the trends in the rest of the economy? How have their market position and impact on the environment changed? The article is based on academic literature and an analysis of the information contained in mandatory reports submitted by the companies, as well as the data from international organisations. The study shows that, despite the pandemic and a severe crisis in the global economy, the companies analysed are doing well - their market values, revenues, net income and headcount are still increasing, which means that GAFA have benefited from the pandemic by further strengthening their position.
Keywords: information economy; digital economy; digital platforms; GAFA; COVID-19